Características agronômicas e teor de óleo de dois híbridos de canola semeados em diferentes épocas no município de Marechal Cândido Rondon - Melgarejo Arrúa, Milciades Ariel (2013)
The objective of this work was to evaluate the influence of different sowing dates on agronomic traits and oil content of canola (Brassica napus L.) crop in 2012. We used a randomized complete block design in a split plot 2 x 7, seven sowing dates: 24/03/12, 07/04/12, 21/04/12, 05/05/12, 19 / 05/12, 02/06/12 and 16/06/12 and two canola hybrids: Hyola 61 and 433. The average population was 252,500 plants per hectare. The advancement in sowing times reduced plant height, number of pods per plant, thousand grain weight, productivity and oil content. The hybrid Hyola 61 showed 9% lower than the number of pods and 5.4% higher in thousand grain weight in relation to Hyola 433 . Grain yield and oil content were similar among treatments, with an average of 1058 kg ha -1 and 38%, respectively. The results allow to infer that the first season of sowing, that is 20/04 may favor the coincidence with environmental conditions favorable to high yields of canola